Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1046/j.1439-0507.1999.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Itraconazole trough concentrations in antifungal prophylaxis with six different dosing regimens using hydroxypropyl‐β‐cyclodextrin oral solution or coated‐pellet capsules

Abstract: We have previously shown that a trough concentration of at least 500 ng ml-1 itraconazole is necessary for an effective antifungal prophylaxis in neutropenic patients. Since the bioavailability of itraconazole is reduced in these patients, a satisfactory dosing regimen remains to be defined. In this study, six dosing regimens with itraconazole capsules 400, 600 or 800 mg day-1, itraconazole solution 400 mg day-1 (additional loading dose: 400 mg day-1 solution for 2 days), 800 mg day-1 or 400 mg day-1 (addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 34 publications
(52 reference statements)
0
55
0
4
Order By: Relevance
“…86 Mold-active triazole antifungal agents (itraconazole, voriconazole, and posaconazole) are the other antifungal class most frequently recommended for TDM because of erratic absorption (itraconazole and posaconazole), variable hepatic clearance (voriconazole), and propensity for multiple drug interactions. 86 Several studies have examined the association between itraconazole efficacy and serum drug levels when the drug is administered as prophylaxis 90,91 or for the treatment 5,92-94 of documented infections due to Candida, Aspergillus, Cryptococcus, and Coccidioides immitis. All of these studies found a higher probability of treatment response when serum trough concentrations determined by bioassay surpassed 6 μg/ mL (>1-2 μg/mL by high-performance liquid chromatography).…”
Section: Therapeutic Drug Monitoring Of Antifungal Agentsmentioning
confidence: 99%
“…86 Mold-active triazole antifungal agents (itraconazole, voriconazole, and posaconazole) are the other antifungal class most frequently recommended for TDM because of erratic absorption (itraconazole and posaconazole), variable hepatic clearance (voriconazole), and propensity for multiple drug interactions. 86 Several studies have examined the association between itraconazole efficacy and serum drug levels when the drug is administered as prophylaxis 90,91 or for the treatment 5,92-94 of documented infections due to Candida, Aspergillus, Cryptococcus, and Coccidioides immitis. All of these studies found a higher probability of treatment response when serum trough concentrations determined by bioassay surpassed 6 μg/ mL (>1-2 μg/mL by high-performance liquid chromatography).…”
Section: Therapeutic Drug Monitoring Of Antifungal Agentsmentioning
confidence: 99%
“…55 Variations in gastric acidity and the widespread use of proton pump inhibitors in HSCT recipients may decrease absorption of itraconazole. Therefore, use of itraconazole oral solution in these patients, which produces higher serum trough concentrations, 56 is preferred.…”
Section: Triazole Antifungalsmentioning
confidence: 99%
“…Multiple studies have explored whether these variations have clinical consequences in terms of efficacy. Itraconazole oral formulations have been seen to have variable bioavailability in multiple studies [141][142][143][144][145]. Higher doses appear to have greater antrifungal effects in both animals and humans [141,[145][146][147][148] .…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Itraconazole oral formulations have been seen to have variable bioavailability in multiple studies [141][142][143][144][145]. Higher doses appear to have greater antrifungal effects in both animals and humans [141,[145][146][147][148] . Voriconazole , when taken orally also has been shown to havevariable bioavailability, especially in HCT recipients [149][150][151].Voriconazole is metabolized in the liver via the cytochrome P450 dependent mechanism, predominantly by CYP2C19 isoenzyme which exhibits genetic polymorphism resulting in reduced drug metabolism in 15-20% patients of Asian descent, and 3-5% of Caucasians and Blacks [150].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%